Environmental Hydraulic Impacts of River Diversions into An Impoundment (Malaysian Journal of Civil Engineering, 2017)
The Drainage and Irrigation Department, Malaysia (DID) is planning on flow diversions of Gombak and Batu Rivers into an ex-mining Batu pond as one of flood mitigation measures in the urbanizing Klang River basin. The pond will also be used for recreational activities during non-flooding period. An impact study on the pond has been carried out using a 2-D hydrodynamics and water quality model which concentrates on the transport of total suspended solids (TSS). Active flow activities and pollutant transport take place mostly in the southern region of the pond resulting the water to be unfit for the designated use.